Navigating Romantic Loss: A Phenomenological Study of Emotional Distress, Coping, and Recovery Following a Romantic Breakup - Rijal Abdillah; Shazia Shahzadi (Grief and Trauma, 2026)
Romantic relationship dissolution (heartbreak) is a common yet psychologically significant event in early adulthood. Prior research on its aftermath has been dominated by quantitative studies examining associations among emotion regulation, rumination, self-compassion, and psychological well-being, leaving the lived experience of recovery relatively underexplored, particularly within Indonesia’s collectivist culture. This study explored the lived experience of emotional recovery following a romantic breakup among young adult women in Indonesia. A qualitative study using a descriptive phenomenological design and Colaizzi’s seven-step method (Morrow et al., 2015) was conducted. Three participants (SIM, 19; HAN, 19; ZA, 20) who reported experiencing emotional recovery following a breakup, along with two key informants (RO, 21; BRI, 22), were recruited through purposive sampling. Data from in-depth interviews, participant observation, and document analysis were analyzed using Colaizzi’s seven-step phenomenological procedure; informant data were used for triangulation rather than as independently reported findings. Six interrelated themes emerged: the emotional impact of the breakup, rumination, emotional regulation and coping strategies, social support, the process of recovery, and emotional recovery. Recovery unfolded gradually through cumulative turning points rather than a single moment of closure. Peer support played a more central role than family support, while behavioral recovery did not always coincide with full emotional resolution, as illustrated by one participant’s persistent resentment despite resuming normal daily functioning. Interventions following a breakup should therefore address emotional resolution and forgiveness rather than functional recovery alone. These findings highlight the value of phenomenological inquiry for understanding recovery processes that variable-centered quantitative research may not fully capture.